1996
DOI: 10.1557/proc-465-879
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Plutonium Interacting with Bentonite and Sulfate-Reducing Anaerobic Bacteria

Abstract: The interactions between sulfate reducing anaerobic bacteria and plutonium, with or without bentonite present, were investigated using distribution coefficients {Kd (mlig)} as an index of the radionuclide behaviour. Plutonium Kds for living bacteria varied within a large range, from 1,804 to 112,952, depending on the pH, while the Kds ranged from 1,180 to 5,931 for dead bacteria. In general, living bacteria had higher plutonium Kds than dead bacteria. Furthermore, the higher Kd values of 39,677 to 106,915 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…at pH 5.0, consistent with studies of growing cultures of halophiles at pHs 6 and 8 in which only 2.5 to 9% of the Pu was associated with biomass [6]. Kudo et al [28] examined the uptake of Pu (10 −17 M) by sulfate-reducing bacteria and found that living cells sorbed more than dead cells. This study shows that the near-and far-field repository environments investigated harbor viable microbial populations capable of actinide uptake.…”
Section: Discussionsupporting
confidence: 72%
“…at pH 5.0, consistent with studies of growing cultures of halophiles at pHs 6 and 8 in which only 2.5 to 9% of the Pu was associated with biomass [6]. Kudo et al [28] examined the uptake of Pu (10 −17 M) by sulfate-reducing bacteria and found that living cells sorbed more than dead cells. This study shows that the near-and far-field repository environments investigated harbor viable microbial populations capable of actinide uptake.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, insoluble plutonium hydroxides are precipitated on the bacterial surfaces, and/or Pu 4+ is sorbed by the functional groups thereon. Kudo et al (37) reported that the distribution coefficient (Kd) of Pu for a mixture of bacteria and bentonite, a backfill material for isolating radioactive wastes, was nearly the same as that of bacteria alone, whether the bacteria were sterilized (killed) or not. However, they did not measure the chemical states of Pu throughout the sorption experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The Kd values were measured under the following four conditions: sterilized bacteria in distilled water, non-sterilized bacteria in distilled water, a mixture of sterilized bacteria and bentonite in distilled water, and a mixture of non-sterilized bacteria and bentonite in distilled water. We used non-sterilized bentonite for the bacteria interaction, because there were no great differences in Kd values between sterilized and non-sterilized bentonite [18].…”
Section: Correlation Between the Plutonium Kd Value And Bacterial Actmentioning
confidence: 99%